Kekerasan sebagai Kisah: Visualisasi Konflik Israel-Palestina dalam Novel Grafis Palestine dan Footnotes in Gaza - Saputra, Reno; Iqbal, Muhammad; Husni, Muhammad (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2023)
This article examines the visualization of violence experienced by the Palestinian people against Israeli occupation in the Graphic Novel by Joe Sacco. This study is literature research using David Wasterfors' social theory of